Neuro-fuzzy equalizers for mobile cellular channels - Raveendranathan, K. C. (Boca Raton, FL : CRC Press, Taylor & Francis Group, 2014)
"This book introduces the concepts of channel equalizers for cellular channels. Modeling and simulation of wireless channels forms part of the discussion. The book begins with a brief introduction to mobile wireless channels and their equalization. It then gives a detailed discussion on contemporary equalization schemes, with reference to the vast literature in this area. The author carefully brings in the concept of neuro-fuzzy channel equalization and discusses various types. "--
Includes bibliographical references and index.
Keywords: Wireless communication systems; Mobile communication systems; Fuzzy systems; Neural networks (Computer science); COMPUTERS / Networking / General; TECHNOLOGY & ENGINEERING / Mobile & Wireless Communications